Medical insurance, community rating, and adverse selection: an overlapping generations perspective - Somerville, R. A. (Economic & Social Studies, 1998)
This paper analyses the demand for medical insurance using an overlapping generations model. It is shown that the rate of interest and the age structure of the insured population jointly determine whether a typical fully insured individual prefers a community-rated premium structure to experience rating, assuming monopoly supply with a zero-profit constraint. Conditions are derived in which community rating leads to inter-generational adverse selection, and it is found that the impact of premium changes on adverse selection depends on the values of the coefficient of absolute risk aversion over the entire life cycle. Finally, it is suggested that the conclusions on adverse selection are currently relevent to the market for medical insurance in Ireland.
Keywords: Medical insurance; Community rating; Ireland